Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content: 1. Review of Identity in The Gypsy by Weam Almadady Prof. Adnan Mahmoud Suleiman Obaidat 2. Image of The Jew in “Sleep of the Gazelles” Mr. Farid Khalil Nassar 3. Renovation Regarding The Origin Of Subject Indication Concerning Al-Ragib Al-Asfahani Mrs. Wafaa Mohamed Elshahed 4. The effect of semantic contrast on text interpretations in the exegesis of Al-Zamakhsharī Dr. Alhassan Abdur-Rahim Husein 5. Metasardic themes in the novels of Amir Taj Al-Sir Mr. Hossain Torfi Alivi, Co-Prof. Ali Khezri, Prof. Rasoul Balavi, Co-Prof. Mohammad Javad Pur Abed 6. The Semiotics of Emotions in Diwan (wtar unajy kawsah) By Maher’s Mahl Alrehaily Prof. Alreem Mufwaz Alfawaz, Mrs. Mrwa Mokhtar Elgheity 7. The significance of the command verb and the compatibility of the Quranic comma Mr. Saad Faiz Khamis Almahaijri